Pengaruh Kepemimpinan Kepala Sekolah, Profesional Guru dan Budaya Kerja Terhadap Kinerja Guru Sekolah Dasar Negeri di Kecamatan Sibolga Utara - Franky Parlindungan Silalahi; Amini Amini (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to analyze the influence of principals' leadership, professional teachers, work culture on the performance of elementary school teachers in North Sibolga district and the influence of principals' leadership, professional teachers and work culture together on the performance of elementary school teachers in North Sibolga district. The population in this study were all PNS teachers who had been certified at SDN in North Sibolga District, amounting to 55 people. Methods of data collection using a questionnaire. Furthermore, validity and reliability tests were carried out. The data analysis technique used is multiple linear regression, hypothesis testing, and coefficient of determination. The results showed that: (a) The relationship of the principal's leadership variable (X1) to teacher performance (Y) in the regression equation Y = 50,002+ 0,497 JMP-DMT, 4(2), 2023 | 46X1. This means that if the school climate increases by 1 point, the teacher's performance will increase by 0,497 points at a constant of 50,002. The value of R square is 0,333 meaning that there is an influence of Principal Leadership on Teacher Performance by 33,3% (b) The form of the relationship of teacher professional variables (X2) to teacher performance (Y) in the form of a regression equation Y = 65,455 + 0,529 X2. This means that if the Organizational Structure increases by 1 point, the teacher's performance will increase by 0.529 points at a constant of 65,455. The value of R square is 0,426, this means that there is an influence of teacher professional variables (X2) on teacher performance by 42,6% (c) The form of the relationship between work culture variables (X3) on teacher performance (Y) in the form of a regression equation Y = 65,455 + 0,306 X3. This means that if the organizational structure increases by 1 point, the teacher's performance will increase by 0.306 points at a constant of 65,455. So Ha is accepted and Ho is rejected. The value of R square is 0.175. This means that there is an influence of work culture (X3) on teacher performance of 17,5% (d) because Fcount Ftable or 16,633 2,790. The value of R square is 0.934, meaning that there is an effect of principal leadership, teacher professional and work culture together on teacher performance of 93,4% Ha accepted and Ho rejected.